Fast Then Slow: Choice Revisions Drive a Decline in the Attraction Effect - Crosetto, Paolo; Gaudeul, Alexia (Management Science, 2024)
We explore the nature and robustness of the attraction effect. The attraction effect can be seen as a persistent bias or as the result of heuristics that may not persist upon reflection. We provide robust experimental evidence that the attraction effect first rises and then falls over time when participants are incentivized to make a quick choice they can later revise. Participants in two experiments under continuous time pressure make choices among options with the aim to maximize an objective, measurable value. We find that participants disproportionately favor the asymmetrically dominant option in the first seconds and then revise their choices until the effect disappears or is significantly reduced. The effect survives only in the special and often studied case of indifference among options. We develop a tractable extension to the multiattribute linear ballistic accumulator model to allow for choice revisions. That model explains how choice revisions reduce context effects. We estimate its parameters at the individual level and document differences between fast and slow participants that also play a role in explaining the rise-and-fall pattern in the attraction effect. We extend the analysis to similarity and compromise effects. We find a very small similarity effect, which does not exhibit any dynamics, and a significant reverse compromise effect displaying a rise-and-fall pattern. Our findings, although limited to objective-value tasks, are consistent with context effects being short-term heuristics that can be superseded by more reflective cognitive strategies when decision makers have time and incentive to do so. This paper was accepted by Manel Baucells, behavioral economics and decision analysis. Funding: This work was supported by the Institut National de la Recherche Agronomique [Grant SAE2 Jeune Chercheur 2017]. Supplemental Material: The data files and online appendix are available at https://doi.org/10.1287/mnsc.2023.4874 .